DETERMINANTS OF EFFECTIVE TAX BURDEN OF SELECTED COMPANIES IN THE USA : DOI: 10.5937/etp2402023B - Bakić, Sanja (Ekonomija - teorija i praksa, 2024)
Taxes and spending policies represent the focus of public finance, an area of economics. Studying corporate income tax is a key part of public finance research. Profits generated by specific companies, whether public or private, are subject to a national direct tax known as corporate income tax. The aim of this research is to determine the impact of macroeconomic and microeconomic variables on the effective tax burden using examples of companies from the agrarian industry, communication industry, banking industry, and pharmaceutical industry. The research covers the period from 2013 to 2022. Finally, empirical estimates using dynamic panel analysis through the GMM model indicate that determinants such as company size, financial leverage, ROA, and inflation rate affect the effective tax burden, while the GDP variable was not found to be statistically significant. The limitations of the research relate to the inability to generalize the obtained results to companies from other industrial sectors. The findings of this research provide important information for investors, economic policy makers, and other economic entities.